Human dental follicle mesenchymal stem cells alleviate T cell response in inflamed tissue of Crohn’s patients - Zibandeh, Noushin; Genc, Deniz; Duran, Yazgul; Banzragch, Munhtsetseg; Sokwala, Sakina; Goker, Kamil; Atug, Ozlen; Akkoç, Tunç (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Crohn’s Disease (CD) is a chronic inflammatory condition characterized by various abnormalities that lead to overly aggressive T-cell responses. Our in vitro experiments aimed to investigate the potential use of Dental Follicle Mesenchymal Stem Cells (DF-MSCs) to suppress the exaggerated immune response in inflamed and non-inflamed tissue of Crohn’s Disease (CD).Material and Methods: Dental follicle tissues were obtained from extracted third molar teeth of 3 healthy volunteers who have no abscess or inflammatory diseases. Eleven patients included the experiment who had been diagnosed with CD and not received steroid maintenance therapy for more than 1 month. Mononuclear Cells (MNCs) were isolated from inflamed and non-inflamed tissue of CD. Isolated cells were stimulated with anti-CD3/anti-CD28 monoclonal antibodies in the presence and absence of DF-MSCs and analyzed for lymphocytes proliferation capacity and viability, T lymphocyte subsets, CD4+IL22BP and CD4+CD25+Foxp3+ regulatory T cell (Tregs) frequencies and cytokine levels.Results: A significant downregulation of lymphocyte proliferation and CD4+IL22BP T cell ratio were found in inflamed cultures with DF-MSCs (p<0,005). Also, the frequency of Tregs increased with DF-MSCs (p<0,05). Pro-inflammatory cytokine levels (TNF-α and IL-6) were decreased (p<0,05) and IL-10 levels were increased (p<0,05) in the supernatant of inflamed cultures.Conclusion: DF-MSCs reduced the inflammatory immune response, induced Tregs and downregulated CD4+IL22BP T cell ratio in inflamed samples of CD patients, which may be exploited for significant therapeutic use.